Verlässliche Wissenschaft Bedingungen, Analysen, Reflexionen - Miller, Katharina; Valeva, Milena; Prieß-Buchheit, Julia (Wissenschaftliche Buchgesellschaft (wbg), 2022)
Reliable science supports modern societies. For this, scientific integrity is essential. This anthology highlights the various facets of reliable science and reflects, among other things, professionalization, responsibility, use of AI in scientific practice, guidelines and equality in research.